Carville : remembering leprosy in America - Gaudet, Marcia G. (ACLS Humanities E-Book., 2004)
Mysterious and misunderstood, distorted by biblical imagery of disfigurement and uncleanness, Hansen's disease or leprosy has all but disappeared from America's consciousness. In Carville, Louisiana, the closed doors of the nation's last center for the treatment of leprosy open to reveal stories of sadness, separation, and even strength in the face of what was once a life-wrenching diagnosis. Drawn from interviews with living patients and extensive research in the leprosarium's archives, Carville: Remembering Leprosy in America tells the stories of former patients at the National Hansen's Dise.